INFLUENCE OF MELTING TECHNOLOGY IN SHORT-FLAME ROTOR FURNACE ON COMPOSITION OF POWDER-GAS EMISSIONS - B. M. Nemenenok; G. A. Rumjantseva; L. V. Tribushevskij; S. P. Zadrutskij (Литьë и металлургия)
It is shown that processes of unprepared recycled material melting and of refining processing make ecological danger. That is why one of the variants of ecological safety of refining processes is development and application of more low-toxic preparation and refining alloys.